Efficacy of Ozonated Water Against Erwinia carotovora subsp. carotovora in Brassica campestris ssp. chinensis. (4th March 2017) - Guo, Zhenghong; Wang, Quanxi
ABSTRACT: Erwinia carotovora subsp. carotovora ( Ecc ) is a bacterial pathogen that causes decay of vegetables and is found in a wide range of Brassica crops in the Shanghai area, particularly in non-heading Chinese cabbage (NHCC). In this study, aqueous ozone was used as an antimicrobial agent to prevent the growth of Ecc bacterial colonies. Ecc that were treated with aqueous ozone were completely inactivated after the bacteria had been exposed to 0.5 mg/L ozone at 28 °C. Furthermore, a susceptible NHCC cultivar was directly sprayed with different concentrations of dissolved ozonated water as a pesticide substitute. The effects of the treatments on morphology were analyzed, and some treatments were characterized by induction of visible symptoms of senescence. No negative effects were observed after treatment by spraying ozonated water compared with the control at concentrations below 8 mg/L. However, visible damage to leaves was observed after the plants were exposed to 10 mg/L ozonated water via spraying for 15 days during the plant reproductive stage. Additionally, enzyme activities and antioxidant responses gradually increased to a certain degree and then decreased in the untreated and ozonated water-treated plants. These results showed that ozonated water was effective in restraining pathogens and potentially defending against disease in growing NHCC plants within a certain concentration range. These results provide a theoretical basis for preventing disease by applying ozonated water to vegetables as an alternative to pesticides.